Implementing remote teaching in response to the COVID-19 crisis: Enabling factors and challenges experienced by three Ghanaian teacher educators - Ngcobo, A. Z.; Enu, J.; Nkum, D. K. (South African Journal of Higher Education, 2022)
The emergence of COVID-19 across the globe has redefined education and technology. The purpose of this article is to report on teacher educators’ conception and experiences of remote teaching. Understanding teacher educators’ conception is significant because one’s conception does influence one’s practices. In addition, understanding the enabling factors and challenges encountered would be of benefit in designing sustainable instructional practices to enhance the quality of online teaching and learning. Data presented here was generated from three Ghanaian teacher educators through semi-structured interviews. While the sample is small the findings are crucial for the enhancement of the current higher education policy practices. Based on the findings it could be argued that teacher educators’ conception of remote teaching as a temporary substitute for traditional face-to-face teaching suggest that they do not view it as something that could be sustained for a longer period. While they consider this form of teaching to be a temporary substitute they all agree that it has some advantages. For example, teaching using online platforms is not restricted by venue constraints thus teaching large classes is more possible and assist with recovering lost time since the teaching mode of teaching can be synchronous and asynchronous. While managing larger classes and recovering lost time was considered a major advantage of remote teaching, teacher educators alluded to the fact that being trained to use the online tools does not equip them with pedagogies to teach. Thus, there is a need to enhance policies to ensure that teacher educators are well equipped with the online pedagogies to ensure that quality teaching is not compromised. In addition, the system factors (e.g., the high cost of data and unstable Internet connectivity) are considered barriers to the effective implementation of remote teaching. The findings of this study have implications for the sustainability of remote teaching not only in underdeveloped countries but globally because the ill-preparedness of teacher educators with the pedagogies of remote teaching means that the quality of education offered to students might not be of an acceptable standard. In addition, the system factors do not only hinder teaching but also add to the burden already experienced with losing teaching and learning time. The insight from this article can help advance the debates about the sustainability of remote teaching.